2022
DOI: 10.1039/d2se00049k
|View full text |Cite
|
Sign up to set email alerts
|

Coordination polymer-derived Al3+-doped V2O3/C with rich oxygen vacancies for an advanced aqueous zinc-ion battery with ultrahigh rate capability

Abstract: It was synthesized [Me2NH2]V3O7 solvothermally, which possesses 2D [V3O7]- anionic layer with interlayer [Me2NH2]+ cation. After cation exchange and the subsequent annealing, it was obtained Al3+, Mn2+ or Zn2+-doped V2O3/C...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Besides, oxygen‐deficient Al 3+ ‐doped V 2 O 3 /C was obtained via ion exchange and ensuing annealing. [ 132 ] During the initial charge, Al 3+ ‐doped V 2 O 3 /C would totally transform to Al 3+ ‐doped Zn 3 (OH) 2 V 2 O 7 2H 2 O. It is revealed that the doped Al 3+ in Zn 3 (OH) 2 V 2 O 7 2H 2 O made for lower binding energy and diffusion of Zn 2+ , leading to good rate performance and long‐term cycling stability.…”
Section: Defects Engineering On V‐based Compoundsmentioning
confidence: 99%
“…Besides, oxygen‐deficient Al 3+ ‐doped V 2 O 3 /C was obtained via ion exchange and ensuing annealing. [ 132 ] During the initial charge, Al 3+ ‐doped V 2 O 3 /C would totally transform to Al 3+ ‐doped Zn 3 (OH) 2 V 2 O 7 2H 2 O. It is revealed that the doped Al 3+ in Zn 3 (OH) 2 V 2 O 7 2H 2 O made for lower binding energy and diffusion of Zn 2+ , leading to good rate performance and long‐term cycling stability.…”
Section: Defects Engineering On V‐based Compoundsmentioning
confidence: 99%
“…Different forms of V-based oxides such as VO 2 , 24 V 2 O 5 , 25 V 2 O 3 , 26 V 6 O 13 , 27 etc . have been used in ZIBs.…”
Section: Introductionmentioning
confidence: 99%